Techno-economic assessment of SEWGS technology when applied to integrated steel-plant for CO2 emission mitigation. (March 2020) - Manzolini, G.; Giuffrida, A.; Cobden, P.D.; van Dijk, H.A.J.; Ruggeri, F.; Consonni, F.
Highlights: The integration of SEWGS to iron and steel industry is investigated. SEWGS is applied to the power section in an iron and steel plant. SEWGS can half the CO2 emissions from the power section with respect to MEA. The SPECCA of SEWGS is as low as 1.9 GJ/tCO2 which is 30 % lower than MEA. SEWGS can reduce the cost of CO2 avoided down to 33 €/tCO2 . Abstract: Mitigation of CO2 emissions in the industrial sector is one of the main climate challenges for the coming decades. This work, carried out within the STEPWISE H2020 project, performs a preliminary techno-economic assessment of the Sorption Enhanced Water Gas Shift (SEWGS) technology when integrated into the iron and steel plant to mitigate CO2 emissions. The SEWGS separates the CO2 from the iron and steel off-gases with residual energy content (i.e. Blast Furnace Gas, Basic Oxygen Furnace Gas and Coke Oven Gas) and the produced H2 is sent to the power generation section to produce the electricity required by the steel plant, while the CO2 is compressed and transported for storage. Detailed mass and energy balances are performed together with a SEWGS cost estimation to assess the energy penalty and additional costs related to CO2 capture. Results demonstrates the potential of SEWGS to capture over 80 % of CO2 in the off-gases, which results in entire plant CO2 emission reduction of 40 % with a Specific Energy Consumptions for CO2 Avoided (SPECCA) around 1.9 MJ/kgCO2 . SEWGS outperforms a commercial amine scrubbing technology which has a SPECCA of 2.5 MJ/kgCO2 and only 20 % of CO2 avoided. The cost of CO2 avoided calculated on the basis of a fully integrated steel plant is around 33 €/tCO2 compared to 38 €/tCO2 of the amine technology.